Síntese de padrões cromatográficos e estabelecimento de método para dosagem da composição de ésteres de ácidos graxos presentes no biodiesel a partir do óleo de babaçu Synthesis of chromatographic standards and establishment of a method for the quantification of the fatty ester composition of biodiesel from babassu oil - Daniele Urioste (Química Nova, 2008)
Several alkyl esters were synthesized, purified, characterized by ¹H NMR and employed as standards for establishing chromatographic methods to monitor their formation in the synthesis of biodiesel. The efficiency of the chromatographic methods was confirmed with the products of enzymatic transesterification of babassu oil with different alcohols (C2 to C4), using Lipozyme as catalyst.